Does digital financial inclusion matter for economic growth and environmental sustainability in OBRI economies? An empirical analysis - Ozturk, Ilhan; Ullah, Sana (Resources, conservation and recycling, 2022)
Digital financial inclusion has become a significant development strategy in many economies, and related research is increasing. Promoting digital financial inclusion and increasing economic growth and environmental quality are main, but challenging priorities in the one belt and road initiative (OBRI) region. This paper studied the impacts of digital financial inclusion on economic growth and environmental sustainability in 42 OBRI countries from 2007 to 2019. The empirical analysis is based on pooled ordinary least squares (OLS), two-stage least squares (2SLS) and generalized method of moments (GMM) approaches. The empirical finding showed that digital financial inclusion increases economic growth but decreases environmental quality through the surge of CO₂ emissions. Thus, the policymakers in OBRI regions should formulate such policies that improve digital financial inclusion in order to achieve economic performance and environmental sustainability.